2016
DOI: 10.2485/jhtb.25.345
|View full text |Cite
|
Sign up to set email alerts
|

Individual Variations in the Hardness and Elastic Modulus of the Human Cementum

Abstract: The purpose of this study was to measure the physical properties of enamel and cementum of permanent teeth and to determine the correlation between them. This study was conducted on 50 maxillary premolars that were collected from 26 orthodontic patients (10 males and 21 females, mean age: 19.51 years, range: 12-35 years). The hardness and elastic modulus of the enamel and cementum were measured at the surface of the crown and root at three locations (cervical third: CC, middle third: CM, and apical third: CA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Dentin has ∼60% hydroxyapatite, where cementum has between 45 and 50% (Ho et al, 2004;Srivicharnkul et al, 2005;Goldberg, 2011;FIGURE 4 | Plot of the average normalized changes in volume for the enamel and cementum/dentin vs. the cumulative brushing time (in minutes). Yamaguchi et al, 2016) The high mineral content of the enamel, over 90% (Habelitz et al, 2001;Goldberg et al, 2014;Yilmaz and Schneider, 2016), results in significant contrast to the cementum and dentin. Therefore, it is not possible to indicate when the abrasive behavior of the tooth brushing has completely removed the cementum and then begun to remove the underlying dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Dentin has ∼60% hydroxyapatite, where cementum has between 45 and 50% (Ho et al, 2004;Srivicharnkul et al, 2005;Goldberg, 2011;FIGURE 4 | Plot of the average normalized changes in volume for the enamel and cementum/dentin vs. the cumulative brushing time (in minutes). Yamaguchi et al, 2016) The high mineral content of the enamel, over 90% (Habelitz et al, 2001;Goldberg et al, 2014;Yilmaz and Schneider, 2016), results in significant contrast to the cementum and dentin. Therefore, it is not possible to indicate when the abrasive behavior of the tooth brushing has completely removed the cementum and then begun to remove the underlying dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the abovementioned results, individual variations in the hardness and Ca/P ratio of cementum may influence the resistance or susceptibility to root resorption and could be involved in root resorption caused by orthodontic forces. Yamaguchi et al [5] demonstrated a positive correlation between the respective hardness of enamel and cemen-tum in humans (hardness: r = 0.551, p < 0.01, and elastic modulus, r = 0.552, p < 0.01). If cementum hardness can be estimated based on the value of enamel, it may be possible to accurately evaluate the risk of root resorption in each patient during orthodontic treatment.…”
Section: The Difference Of Chemical Composition Of Cementummentioning
confidence: 98%
“…The hardness (soft, moderate, and hard) and tissue mineral density (TMD) of the cementum in the apical region of the root have been measured using the dynamic micro-indentation method and X-ray µCT analysis, respectively. The cementum hardness values were lower in the soft and moderate groups than in a hard group [5], and the X-ray µCT analysis revealed that the teeth in the hard group had higher TMD values than those in the other two groups [6]. Therefore, the hardness of the cementum may be related to the occurrence of ORR.…”
Section: Involvement Of Cementum In Orr 71 the Hardness Of Cementummentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-specific factors causing root resorption include allergies(1), chronic asthma (2), abnormal root (3), and the hardness and form of cementitious materials (4).…”
Section: Introductionmentioning
confidence: 99%